CFD-based investigation of energy and exergy enhancement in a geothermal heat exchanger with hybrid nanofluid and novel turbulator - As'ad Alizadeh; Joy Djuansjah; Ali Basem; Aman Sharma; Muntadher Abed Hussein; Husam Rajab; Khalil Hajlaoui; R. Thakur (Case Studies in Thermal Engineering)
In this study, a three-dimensional geothermal heat exchanger is modeled using computational fluid dynamics. To enhance thermal performance, the middle section is equipped with turbulators of various twist ratios (λ = 0, 0.85, 1.70, and 2.55). The Syltherm 800-Al2O3/DWCNT hybrid nanofluid is used at volume fractions (φs) of 0 %, 1.5 %, and 3.5 %. The turbulent flow regime is considered within a Reynolds number (Re) range of 23,000 to 92,000 and is simulated using the k−ω SST turbulence model. The SIMPLE algorithm is used for pressure–velocity coupling, and the Least Squares Cell-Based method is applied for spatial discretization. Results show that the hybrid nanofluid and turbulators significantly enhances both thermal and exergetic performance. The average Nusselt number, pressure drop, and performance evaluation criterion (PEC) are strongly affected by λ, φ, and Re. For λ = 2.55, φ = 3.5 %, and Re = 92,000, the Nusselt number increases by 52.78 %, while pressure drop rises by 65.77 % compared to the unmodified GHE. Despite this, PEC remains above 1 in all cases, with a maximum of 1.395 at Re = 25,000. Exergy efficiency shows a maximum improvement of 19.63 % at φ = 3.5 % and λ = 0.